Cross-cultural communication across STEM disciplines - Ma, Taejung; Lucietto, Anne M. (Frontiers in Education, 2024)
Collaboration across cultures in Science, Technology, Engineering, and Math (STEM) fields has become increasingly common. This means many STEM professionals in US-based companies now work with professionals from other cultures. In this global context, cross-cultural knowledge is crucial for effective communication. Without this knowledge, there can be misunderstandings and discomfort. Different cultures use different communication styles, which has been studied by the field of communication. The concept of high and context low-context culture is used to discuss the role of contextual cues in communication. High-context cultures rely on implicit language and contextual and situational cues, while low-context cultures use explicit language. Although no culture is strictly high or low context, this concept is important as it helps us understand how our communication style can be influenced by cultural characteristics.There is a growing need to support and encourage students to become interested in pursuing careers in STEM fields. Many STEM programs in the United States have emphasized the importance of collaboration to meet this need. However, effective collaboration requires effective communication, and students often lack opportunities to explore how they can communicate effectively with collaborators from other cultures and countries. To bridge this gap, this article proposes incorporating communication into STEM courses for undergraduate students. The course will include learning opportunities about low and high-context cultures and guest speakers. This article aims to provide insights into how communication content can prepare undergraduate students to become culturally competent STEM professionals.